2021
DOI: 10.3847/1538-4357/abd324
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Blazar Candidates from the 3FGL Unassociated Catalog into BL Lacertae Objects and Flat Spectrum Radio Quasars Using Swift and WISE Data

Abstract: We utilize machine-learning methods to distinguish BL Lacertae (BL Lac) objects from flat spectrum radio quasars (FSRQs) within a sample of likely X-ray blazar counterparts to Fermi 3FGL unassociated gamma-ray sources. From our previous work, we have extracted 84 sources that were classified as ≥99% likely to be blazars. We then utilize Swift-XRT, Fermi, and The Wide-field Infrared Survey Explorer (WISE) data together to distinguish the specific type of blazar, FSRQs, or BL Lac objects. Various X-ray and gamma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Using a combination of RF and ANN, Zhu et al (2021) studied 1336 unassociated sources and classified them as 583 AGN-like sources, 115 pulsars, 154 other classes, and 484 of uncertain type. Kaur et al (2021) utilized RF to classify Fermi 3FGL unassociated γ-ray sources as BL Lac objects and FSRQs. A sample of 84 highly likely blazar candidates was then classified as 50 likely BL Lac objects, and 34 were ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of RF and ANN, Zhu et al (2021) studied 1336 unassociated sources and classified them as 583 AGN-like sources, 115 pulsars, 154 other classes, and 484 of uncertain type. Kaur et al (2021) utilized RF to classify Fermi 3FGL unassociated γ-ray sources as BL Lac objects and FSRQs. A sample of 84 highly likely blazar candidates was then classified as 50 likely BL Lac objects, and 34 were ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that FSRQs exhibit a similar SED across a wide range of L γ , while BL Lacs display decreasing synchrotron peak frequencies with increasing L γ . Furthermore, the nature of blazars at various wavelengths has been discussed by several studies (Richards et al 2011;Landi et al 2015;Acciari et al 2021;Kaur et al 2021;Kerby et al 2021).…”
Section: Introductionmentioning
confidence: 99%